Association Between Caregiver's Perception of “Good” Dietary Habits and Food Group Intake Among Preschool Children in Tokyo, Japan - Kano, Mayuko; Tani, Yukako; Ochi, Manami; Sudo, Noriko; Fujiwara, Takeo (Frontiers in Pediatrics, 2020)
Given that parents are mainly responsible for a preschooler’s dietary management, they need to understand a child’s diet. However, few studies have examined the association between parental perception of a preschool child’s “good” dietary habits and actual food intake. We conducted a cross-sectional study investigating whether a child's food intake would differ depending on the caregiver’s perception of their child’s dietary habits among 4-year-old nursery school children at Adachi City, Tokyo, Japan. Children’s dietary data were collected using the brief-type self-administered diet history questionnaire for children Aged 3–6 Years (BDHQ3y), while caregivers’ perceptions of their child’s dietary habits (good, normal, and poor) were inquired (N = 136). The percentage of caregivers who perceived their child’s dietary habit as good, normal, and poor was 41.2%, 40.4%, and 18.4%, respectively. Multiple linear regression analysis revealed that children whose caregivers perceived their diet as poor showed lower intakes of vegetables [β = −48.7, 95% confidence interval (CI): −86.1 to −11.2], beans (β = −13.2, 95% CI: −26.1 to −0.3), and fish and shellfish (β = −9.2, 95% CI: −17.5 to −1.0) and higher intakes of fat and oil (β = 1.7, 95% CI: 0.4 to 3.1), confectionaries (β = 11.9, 95% CI: 3.6 to 20.3), and soft drinks (β = 31.2, 95% CI: 3.5 to 59.0) compared to children whose caregivers perceived their diet as good (all measures are in g/1000kcal per day). No significant difference was observed in other food groups, such as dairy products, an important source of protein and calcium for children. The current study may therefore guide future nutritional education programs for parents of preschool children.